FIRST LANGUAGE INTERFERENCE IN ENGLISH SPEAKING PERFORMANCE OF UNIVERSITY STUDENTS OF MUHAMMADIYAH SORONG (UMS) - Rizal Akib (Universitas Muhammadiyah Sorong, 2017)
The research objective was to find out the interference of first language occurs to English Speaking Performance at English department Students in University of Muhammadiyah Sorong and to find out what kinds of first language interference occurs to English Speaking Performance at English department Students in University of Muhammadiyah Sorong. The research design applied qualitative descriptive analysis which used to analyze the data taken from the real speaking of respondents that recorded on the progress of data collection. Numbers of respondent are asked to give their opinion or responses on selected theme provided on this research to elicit their real speaking performance which is recorded and analyzed. The result of this research revealed that there were first language interference occurred at English department students in university of Muhammadiyah Sorong and several kinds of first language interference were occurred on Word Pronunciation (54%), Dialect (38%), and Word Repetition (8%) which based on 15 respondent and total populations from three semesters of English Department in University of Muhammadiyah Sorong.